2020
DOI: 10.1002/aoc.5569
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Evaluation of the Antibacterial and Antitumor Activity of HalogenatedSalen Copper (II) Complexes derived from Camphoric Acid

Abstract: Platinum metal complexes are the most common chemotherapeutics currently used in cancer treatment. However, the frequent adverse effects, as well as acquired resistance by tumor cells, urge the development of effective alternatives. In the recent past, copper complexes with Schiff base ligands have emerged as good alternatives, showing interesting results. Accordingly, and in continuation of previous studies in this area, three new camphoric acid‐derived halogenated salen ligands and their corresponding Cu (II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…It is worth noting that the true nature of the active sites in many MOFs, including metal ions, is saturated with the coordination of organic ligands (Zou et al, 2007). Copper has more antibacterial and anticancer properties than others (Gu et al, 2017;Pires et al, 2020). The bactericidal mechanism of Cu-MOF is due to the diffusion of Cu 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the true nature of the active sites in many MOFs, including metal ions, is saturated with the coordination of organic ligands (Zou et al, 2007). Copper has more antibacterial and anticancer properties than others (Gu et al, 2017;Pires et al, 2020). The bactericidal mechanism of Cu-MOF is due to the diffusion of Cu 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the free ligand and its metal chelates were more active against Gram‐positive bacteria ( S. aureus ) compared to Gram‐negative bacteria ( E. coli ). [ 95 ] In Gram‐positive bacteria, chelates 4 , 5 , and 6 were highly active with comparable zones of inhibition of 14.3, 14.8, and 14.6 mm, which is almost two times better than the ligand. However, in Gram‐negative bacteria metal chelate 5 was the most active, screening a comparable zone of inhibition of 16.1 mm, displaying better efficiency than the ligand and the other chelates.…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43] In these cases, as in other anticancer drugs, the compounds act under different mechanisms that depend not only upon their molecular descriptors but also upon other multifactorial phenomena that may either converge or not: e. g., metabolic pathway alterations, enzymatic inhibition, nucleic acid intercalation, unnatural allosterism, membrane disruption, etc. In this regard, the effect of introducing bromine groups in Schiff bases to enhance their antiproliferative properties was very recently confirmed in Salen [44][45][46] and Salphen-like [47] metal complexes from mostly Cu(II) and some examples from Fe(III) or Mn(III). In these works, the authors reported that bromine atoms symmetrically incorporated to each of the two o-salicylaldehyde moieties of a single skeleton could render between 12 % and 6-fold lower IC50 values if compared to their non-halogenated complex counterparts, thus facilitating the access to competitive values below 29 μM in different cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%